The BOF5 macroeconomic model of Finland: Structure and equations - Alpo Willman; Mika Kortelainen; Hanna-Leena Männistö; Mika Tujula (Bank of Finland, 1998)
This report is the basic documentation of the present (fifth) version of the Bank of Finland macroeconomic model, BOF5, built for policy simulation and forecasting.In constructing the model, consistent treatment of expectations is emphasized.Following current theoretical literature, intertemporal optimization with rational expectations is taken as the starting point, and Euler equations are applied in the estimation of the key behavioural equations.Consistent treatment of technology on the supply side has been another important aim.We illustrate the properties of the model with some simulation experiments.A complete list of equations and an outline of the derivation of the key equations are presented.We also show how forward-looking equations have been transformed to facilitate simulation under alternative assumptions concerning the formation of expectations.
URN:NBN:fi:bof-20140807164
Keywords: 330; macroeconomic models; Finland; econometric modelling; policy simulations; expectations; Euler equations